2012
DOI: 10.3810/pgm.2012.11.2610
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Approach to Electrical and Pharmacological Cardioversion of Atrial Fibrillation

Abstract: In patients with atrial fibrillation (AF), a rhythm-control strategy may be adopted when there are unacceptable symptoms from AF, failure of rate control, and/or the presence of comorbidities, such as heart failure, that may improve with restoration of sinus rhythm. When a rhythm-control strategy is chosen and the patient is in persistent AF, cardioversion will be necessary to convert the rhythm to sinus. Patients with AF present for > 48 hours must be effectively anticoagulated both prior to and after cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…While other agents are recommended for pharmacological cardioversion by the European Society of Cardiology, their use is often limited by the delayed onset of action and side effects [6,31]. A randomized phase 3 study has shown that in patients with recent-onset AF, Cardiology 2022;147:566-577 DOI: 10.1159/000526831 vernakalant was superior to the widely used amiodarone in terms of cardioversion rate (51.7 vs. 5.2% within 90 min) [24].…”
Section: Discussionmentioning
confidence: 99%
“…While other agents are recommended for pharmacological cardioversion by the European Society of Cardiology, their use is often limited by the delayed onset of action and side effects [6,31]. A randomized phase 3 study has shown that in patients with recent-onset AF, Cardiology 2022;147:566-577 DOI: 10.1159/000526831 vernakalant was superior to the widely used amiodarone in terms of cardioversion rate (51.7 vs. 5.2% within 90 min) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Of the antiarrhythmic medications used by study participants, three are widely known and popular for use in clinical practice worldwide -amiodarone, propafenone and sotalol (Rajagopalan and Curtis, 2012). Extremely limited data is available regarding ethacizine and its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical cardioversion delivers a direct current synchronization with the R wave. It is usually done using external, transcutaneous electrode patches or internal cardiac electrodes [14]. All these treatment strategies have been shown as valuable options in case of postcardiotomy AF [12-14], however so far there has been no evidence regarding efficacy of stepwise escalating therapy using vernacalant, flecainide and EC after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%